2014
DOI: 10.1016/j.yhbeh.2013.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between rapid changes in local aromatase activity and estradiol concentrations in male and female quail brain

Abstract: Estradiol-17β (E2) synthesized in the brain plays a critical role in the activation of sexual behavior in many vertebrate species. Because E2 concentrations depend on aromatization of testosterone, changes in aromatase enzymatic activity (AA) are often utilized as a proxy to describe E2 concentrations. Utilizing two types of stimuli (sexual interactions and acute restraint stress) that have been demonstrated to reliably alter AA within minutes in opposite directions (sexual interactions= decrease, stress= incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 57 publications
4
39
0
2
Order By: Relevance
“…Recently, Dickens et al (2014) reported the acute changes in environmental context that rapidly paralleled region-, sex-and stimulus-specific dynamic changes in aromatase activity, providing evidence for a control of local estrogen concentrations in female quail brain, that are not dependent on ovarian secretion. The authors proposed complex dynamic conditions showing that aromatase activity is affected by experimental conditions and mismatches with local estrogen concentration that are potentially explained by several factors, including -changes in the availability of peripheral testosterone or local testosterone synthesis, time-related differences in aromatase activity and 17β-estradiol levels, localized aromatase-mediated catabolism, and differences between in vivo and in vitro aromatase activity (Dickens et al, 2014).…”
Section: Effects On Steroidogenic Enzyme Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Dickens et al (2014) reported the acute changes in environmental context that rapidly paralleled region-, sex-and stimulus-specific dynamic changes in aromatase activity, providing evidence for a control of local estrogen concentrations in female quail brain, that are not dependent on ovarian secretion. The authors proposed complex dynamic conditions showing that aromatase activity is affected by experimental conditions and mismatches with local estrogen concentration that are potentially explained by several factors, including -changes in the availability of peripheral testosterone or local testosterone synthesis, time-related differences in aromatase activity and 17β-estradiol levels, localized aromatase-mediated catabolism, and differences between in vivo and in vitro aromatase activity (Dickens et al, 2014).…”
Section: Effects On Steroidogenic Enzyme Genesmentioning
confidence: 99%
“…The authors proposed complex dynamic conditions showing that aromatase activity is affected by experimental conditions and mismatches with local estrogen concentration that are potentially explained by several factors, including -changes in the availability of peripheral testosterone or local testosterone synthesis, time-related differences in aromatase activity and 17β-estradiol levels, localized aromatase-mediated catabolism, and differences between in vivo and in vitro aromatase activity (Dickens et al, 2014). The expression of cyp19a was shown previously, not to be modulated after exposure to an EDC (17α-ethynylestradiol: EE2), while cyp19a mRNA levels were significantly reduced by another EDC (nonylphenol: NP) in fish (Lyssimachou et al, 2006).…”
Section: Effects On Steroidogenic Enzyme Genesmentioning
confidence: 99%
“…Increasing evidence indicates that, particularly in the songbird, the concentration of brain androgens is acutely modulated through the regulation of their local synthesis (Pradhan et al, 2010;Heimovics et al, 2016). However, a rapid and reversible reduction in aromatase activity, paralleled by a change in estradiol brain concentration, was measured ex vivo in whole or specific hypothalamus/preoptic area subregions collected immediately after visual or sexual interactions with a female (Cornil et al, 2005;de Bournonville et al, 2013;Dickens et al, 2014), suggesting that aromatase activity is the critical component that determines estradiol availability. aromatase activity is upregulated in distinct brain regions following brief exposure to acute stress (Dickens et al, 2011), an effect that is counteracted by sexual interaction (Dickens et al, 2012).…”
Section: Neurotransmitter-like Effects Of Steroids Estrogens In Birdsmentioning
confidence: 99%
“…While it is true that no estrogen is produced in the absence of aromatase, changes in enzyme activity can result in increases or decreases in tissue estrogen levels with no change in aromatase expression. In fact, such changes have been shown to occur relatively quickly and appear to account for at least some behaviors related to estrogen in the brain of animals (Cornil et al, 2013, Dickens et al, 2014). To gain a complete picture of normal and abnormal changes in regional estrogen synthesis capacity, it would be advantageous to develop radiotracers which are substrates rather than non-competitive inhibitors of the enzyme.…”
Section: Current Limitations and Future Directionsmentioning
confidence: 99%